The Effect of Relationship Marketing and Service Quality Towards Customer Loyalty of PT Bank Perkreditan Rakyat Sumatera Selatan - Marzuki, Marzuki; Wahab, Zakaria; Widiyanti, Marlina; Sihab, Muchsin Saggaff (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to determine whether relationship marketing and service quality affect customer loyalty at Bank BPR Sumsel. This study used a causal research method, an inference research type to realize cause-and-effect, determine the influence of the variables that are the cause (independent variables), and the effect (dependent variable) of a phenomenon. The data used in this study were primary data by distributing questionnaires to deposit customers at the Head Office of the Bank BPR Sumsel. The number of samples used as respondents was 100.Â The data analysis technique used in this study was multiple linear regression analysis, which was previously tested for validity and reliability. The results obtained are relationship marketing and service quality have a positive and significant effect on customer loyalty at the Bank BPR Sumsel.Â From the test results, the R2 (R Square) value of 0.691 or (69.1%) indicated that the percentage contribution of the independent variablesâ€™ (RM and SQ) influence on the dependent variable (customer loyalty) was 69.1%. Alternatively, the independent variables used in the model (RM and SQ) could explain 69.1% of the dependent variable (customer loyalty). Meanwhile, the remaining 30.9% was influenced or explained by other variables not included in this research model such as pricing, brand image, and customer values.